The relationship between motivation and job satisfaction of academics at a University of Technology in Southern Gauteng - Naile, Idah 'Maphalima (Vaal University of Technology, 2015)
The relationship between motivation and job satisfaction at work has been one of the more widely researched areas in the field of management in different professions, but few studies in South Africa have explored these two constructs among academic employees in Higher Education. Although there is a positive relationship between the two constructs, it has been somewhat overlooked by researchers. The objective of this study therefore, is to determine the relationship between motivation and job satisfaction among academic employees at a University. In view of this the researcher seeks to establish whether a there is a relationship between the constructs understudy. The literature study explored the theoretical aspects of motivation and job satisfaction and their relationship. Using a quantitative research approach, the study hypothesised and investigated motivation and job satisfaction in a sample that consisted of 162 academic employees. Two instruments, namely the Work Preference Inventory (WPI) and the Job Satisfaction Survey (JSS), were used to collect the data and determine the existence of a relationship between motivation and job satisfaction. The Statistical Package for Social Sciences (SPSS) version 21.0 for Windows was used to analyse the data; these results are presented and discussed in detail. The study adopted a Confirmatory Factor Analysis technique using Structural Equation Modelling with a Partial Least Squares (semPLS) approach, to measure the relationship by calculating the Cronbach Alpha, the Composite Reliability (CR) value, the Average Value Extracted (AVE), Goodness of Fit and hypotheses. Findings of this study revealed that a significant positive relationship exists between motivation and job satisfaction with the enjoyment variable and job satisfaction reflecting a positive relationship and the other three variables (Challenge, Compensation and Outward Motivation) showing that a negative but significant relationship exists between these three constructs and job satisfaction. It has been recommended that management should look into putting proper motivation and job satisfaction initiatives into place and should also create opportunities for growth by giving academics challenging assignments and providing training and development strategies that will increase their motivation and job satisfaction.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Job satisfaction; Motivation; Academic employees; University of Technology; Dissertations, Academic -- South Africa.; Job satisfaction -- South Africa.; Universities and colleges--Employees -- South Africa.; Employee motivation -- South Africa.; Education, Higher -- South Africa.